2000
DOI: 10.1053/jhep.2000.8106
|View full text |Cite
|
Sign up to set email alerts
|

Isosorbide mononitrate and propranolol compared with propranolol alone for the prevention of variceal rebleeding

Abstract: The aim of this study was to test the effectiveness of isosorbide-5-mononitrate (IM) as an adjunct to propranolol (PR) in the prevention of variceal rebleeding. Ninety-five cirrhotic patients with variceal bleeding were randomly assigned to treatment with PR ؉ IM (46 patients) or PR alone (49 patients). Eighteen patients in the PR ؉ IM group and 28 in the PR group had rebleeding during the 2 years after randomization. The actuarial probability of rebleeding 2 years after randomization was lower in the PR ؉ IM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(61 citation statements)
references
References 26 publications
3
53
1
4
Order By: Relevance
“…Only one study has performed a direct comparison between the combination of propranolol plus ISMN and propranolol alone in patients with prior variceal hemorrhage. 116 This study showed a benefit of combination therapy (33% vs. 41% rebleeding rate), but it was not statistically significant. Data collected from different randomized clinical trials show that the median rebleeding rate in patients treated with combined pharmacological therapy is around 33%-35%, 35,36 lower than that obtained with ␤-blockers alone.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 58%
See 1 more Smart Citation
“…Only one study has performed a direct comparison between the combination of propranolol plus ISMN and propranolol alone in patients with prior variceal hemorrhage. 116 This study showed a benefit of combination therapy (33% vs. 41% rebleeding rate), but it was not statistically significant. Data collected from different randomized clinical trials show that the median rebleeding rate in patients treated with combined pharmacological therapy is around 33%-35%, 35,36 lower than that obtained with ␤-blockers alone.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 58%
“…Therefore, the pharmacological therapy of choice in the prevention of variceal rebleeding is probably the combination of a nonselective ␤-blocker and a nitrate. However, this combination has significantly greater side effects compared to ␤-blockers alone 35,116 and is poorly tolerated in clinical practice so that most patients end up taking ␤-blockers alone.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 99%
“…Pharmacologic therapy includes use of a nonselective β-blocker. 111,[119][120][121][122] Although it has been proposed, 123 combined treatment with isosorbide mononitrate and propranolol is not recommended.…”
Section: Secondary Prophylaxismentioning
confidence: 99%
“…13,14 Combined β-adrenergic blocker and 5-isosorbide mononitrate (BB + ISMN) was more effective than BBs alone in the prevention of esophageal variceal rebleeding. 15,16 It is still unknown whether drug therapy is superior to EBL for preventing variceal rebleeding. Several randomized controlled trials have shown different results.…”
Section: Introductionmentioning
confidence: 99%